Discussion on Etiology and Pathogenesis of Corona Virus Disease 2019 from "Cold-dampness and Insidious Dryness" - Lu Fang-Guo; Wu Tao; Xiao Wen-Ming; Wang Ping; zhao Cheng (KeAi Communications Co., Ltd., 2020)
Based on the characteristics of the epidemic situation and the authors' understanding of the related ancient books and documents, this paper explores the etiology and pathogenesis of Corona Virus Disease 2019 (COVID-19) from 5 aspects: abnormal climate in "warm winter", unique geographical location, pathogenesis evolution of cold and dampness mixed with insidious dryness, transmission and change of "triple energizer" of toxic pathogens, and game between healthy Qi and toxic pathogens. Combined with the special treatment of traditional Chinese medicine (TCM), the purpose is to make a modest contribution to curbing the epidemic situation with TCM. Keywords: 2019 novel corona virus (2019-nCoV), Pneumonia, Pathogenic pathogens of cold and dampness, Game between healthy Qi and toxic pathogen, Hubei Province, Hunan Province